Efficacy of Immediate Post-Partum Intrauterine Contraceptive Device in a Tertiary Care Hospital - Shaista Rashid, Asma Iqbal, Shazia Naseeb, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine efficacy of post-partum intrauterine contraceptive device (IUCD) in women presenting to a tertiary hospital.To compare efficacy of post-partum Intrauterine device between vaginal Insertion and Intra-Cesarean Insertion. Material and Method: A Prospective, cross sectional study was conducted at Department of Gynecology and Obstetrics Unit III, Abbasi Shaheed Hospital, Karachi from Jan2020 to June, 2020. Total 234 patients were included in this study. Patients fulfilling the inclusion criteria were enrolled in the study after taking Informed consent. Copper containing IUCD was inserted. Follow up was done at 6weeks and six months of delivery. All women were counseled to report missing threads, heavy vaginal bleeding, and vaginal discharge with pain in abdomen on each visit during follow-up. Abdominal, speculum and vaginal examinations was done. Efficacy was determined by the expulsion rate. Statistical analysis was done by SPSS Version 20. Results: Out of total insertions 103(44.01%) were intra caesarean and 131 (55.98%) IUCDs were placed after vaginal delivery. Symptoms of unusual vaginal discharge were reported by 28(11.9%) women, missing thread were reported by 67(28.5%), abdominal pain was reported by 92(39.2%) and heavy bleeding was reported by 44(18.8%) patients at follow-up. efficacy of vaginal insertion was 79(60.30%) and intra-cesarean insertion of PPIUCD was 65(63.10%). Conclusion: It can be concluded that PPIUCD in the field of postpartum family planning is a promising approach. Whatever may be the mode of delivery, PPIUCD is safe and effective.